Find New RoadsTM? A Systematic Review on the Impacts of Off-Road Vehicle Activity on Soil, Vegetation, and Wildlife - Ploughe, Laura W.; Fraser, Lauchlan H. (Frontiers in Ecology and Evolution, 2022)
The global use of off-road vehicles (ORVs) in natural environments has accelerated rapidly over the last few decades, resulting in significant social and environmental consequences. As the demand, use, and promotion of light-duty ORVs like all-terrain vehicles (ATVs), motorcycles, four-wheel drive trucks and sport utility vehicles (SUVs) increases in remote wilderness, the landscape is becoming fragmented into disorganized and destructive networks of trails and roads. Substantial ecological impacts to a wide range of ecosystem structures and functions will likely result from ORV activity. Applying a global systematic review, we examine 105 publications about plant, soil, and wildlife responses to ORV traffic in different habitats to help guide the direction of future research, monitoring programs, and mitigation efforts. Most studies investigated impacts to animals, followed by soils, then vegetative responses. Soil studies primarily focused on physical impacts to the soil (i.e., compaction, erosion, rut depth), but some studies suggest that soil chemical and biological properties may also be impacted by ORV traffic. The literature on plant responses to ORV activities primarily explored vegetation loss, although impacts on the plant community were also investigated. Animal studies investigated impacts of ORV use on invertebrates, mammals, birds, and to a lesser extent reptiles/amphibians, including population-level, community-level, and behavioral responses. Overall, research on environmental impacts of ORV traffic is biased to coastal and desert ecosystems in the northern hemisphere (primarily in the US), often does not address mechanisms that may produce ecological impacts (e.g., intensity of vehicular disturbance and ecosystem- or species-specific sensitivity to ORV activities), and frequently focused on short-term responses. More research is needed to understand the mechanisms that cause the different responses of soil, plant, and animals to ORVs over the long-term in a broad range of ecosystems to support real-time management and conservation efforts.